Visual Basic 2012 : - Stephens, Rod (Wiley, 2012)
Microsoft Visual Basic (VB) is the most popular programming language in the world, with millions of lines of code used in businesses and applications of all types and sizes. In this edition of the bestselling Wrox guide, Visual Basic expert Rod Stephens offers novice and experienced developers a comprehensive tutorial and reference to Visual Basic 2012. This latest edition introduces major changes to the Visual Studio development platform, including support for developing mobile applications that can take advantage of the Windows 8 operating system.This new edition includes information on developing Win8-compatible Metro applications using pre-loaded templates. Explores the new design features and support for WPF designers. Explains how to develop Windows smartphone apps. Covers new VB language features such as Asynch and Await